2012
DOI: 10.1007/s00268-012-1546-8
|View full text |Cite
|
Sign up to set email alerts
|

Double Omental Flap Reduced Perianastomotic Collections and Relaparotomy Rates after Pancreaticoduodenectomy with Pancreaticogastrostomy

Abstract: A DOF should be considered a further step toward a reduction of surgical-related complications after PD with PG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Two focused on the surgical technique; two more were written by the same surgical teams, of which we selected the one that included more patients. Finally, we selected 12 articles, which form the basis of our research. Five articles compared groups with and without the use of omentum or FL as wrapping, and the other seven described series of patients in whom some kind of wrapping was performed .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two focused on the surgical technique; two more were written by the same surgical teams, of which we selected the one that included more patients. Finally, we selected 12 articles, which form the basis of our research. Five articles compared groups with and without the use of omentum or FL as wrapping, and the other seven described series of patients in whom some kind of wrapping was performed .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we selected 12 articles, which form the basis of our research. Five articles compared groups with and without the use of omentum or FL as wrapping, and the other seven described series of patients in whom some kind of wrapping was performed . Seven studies were retrospective and five were prospective …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study by Tani et al revealed higher incidence of POPF in omental wrapping group compared to nonwrapping (42.8 % versus 37.3 %) [85]. However, some studies have shown a benefit in reducing the rate of perianastomotic collections [86,87], but their role in reducing the incidence of POPF is questionable and need further studies.…”
Section: Role Of Omentum and Falciform Ligamentmentioning
confidence: 96%